2000
DOI: 10.1046/j.1469-7580.2000.19730413.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation of three‐dimensional microcracks in compact bone

Abstract: Microdamage in bone contributes to the loss of bone quality in osteoporosis and is thought to play a major role in both fragility and stress fractures (Schaffler et al. 1995). In this study, in vivo microcracks in human ribs were bulk-stained in basic fuchsin and viewed in longitudinal section and in 3 dimensions using 2 different computer-based methods of reconstruction : (1) serial sectioning of methylmethacrylate embedded sections using a sledge macrotome and identification of microcracks using UV e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 21 publications
8
92
0
1
Order By: Relevance
“…From the control study carried out it was found that only 25.9% of all preexisting cracks were in vivo cracks. This crack density is low in comparison to in vivo crack densities found in human bone (Burr and Stafford, 1990;Lee et al, 1998;O'Brien et al, 2000) but this is unsurprising as the bone samples were taken from young cattle (2-3 years old) and would be expected to be repaired in vivo very quickly. However, this also shows that less than 5% of all identified microcracks were formed by the machining process.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…From the control study carried out it was found that only 25.9% of all preexisting cracks were in vivo cracks. This crack density is low in comparison to in vivo crack densities found in human bone (Burr and Stafford, 1990;Lee et al, 1998;O'Brien et al, 2000) but this is unsurprising as the bone samples were taken from young cattle (2-3 years old) and would be expected to be repaired in vivo very quickly. However, this also shows that less than 5% of all identified microcracks were formed by the machining process.…”
Section: Discussionmentioning
confidence: 82%
“…Sections 250 µm thick were cut, handground to between 100 and 150 µm and mounted under a glass coverslip. They were examined using epifluorescence microscopy, their cross sectional areas obtained and microcracks identified and measured using the established criteria (Lee at al, 2000a,b;O'Brien et al, 2000). Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Since the first application in studying human cranial bone microstructure by Alan Boyde in 1990, 3 confocal microscopy has become a powerful tool in research related to the skeletal system, such as assessment of bone microdamage under physiological and pathological conditions. [4][5][6] Confocal microscopy has also provided opportunities to investigate bone cell-to-cell interactions in three-dimension, which is particular important for research involving osteocytes and osteoblasts. [7][8][9][10][11] More recently using revised and improved bone processing strategy, a significant progress has been made in the imaging of the bone marrow microenvironment and particularly the vasculature in bone.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional images of single microcracks in trabecular (Fazzalari, et al, 1998) and cortical bone (O 'Brien, et al, 2000), obtained by reconstructing serial sections of two-dimensional confocal microscopy images, demonstrated that cracks were elliptical in shape (O 'Brien, et al, 2000). This technique is powerful for evaluating individual cracks or damaged regions, but can provide only limited information on the spatial distribution of microdamage, because the observation depth is limited to about 160 μm from the surface (Fazzalari, et al, 1998;O'Brien, et al, 2000) and the field of view is small. Microdamage due to non-uniform loading modes, such as torsion, has been studied by accounting for changes in the strain level (Wang, X and Niebur, 2006; Wang, X S, et al, 2005), but was again limited to a few two-dimensional sections for each test specimen.…”
Section: Introductionmentioning
confidence: 99%